1318 Trends in occupational diseases in finland 1975–2013. (24th April 2018) - Sauni, Riitta; Oksa, Panu; Talola, Nina; Virtanen, Simo; Nevalainen, Jaakko; Uitti, Jukka
Abstract : Introduction: The objective was to investigate trends in the incidence of recognised and suspected cases of occupational diseases in Finland 1975–2013, including variations by gender and industry. Methods: The data consisted of recognised and suspected cases of occupational diseases registered in the Finnish Registry of Occupational Diseases (FROD) in 1975–2013. From the annual workforce statistics and data of FROD we calculated the incidence of occupational diseases and suspected occupational diseases per 10 000 employed. For time trends by industrial sector, we used a five-year moving average and Poisson's regression analysis. Results: Annual average rates of occupational diseases (per 10 000 employees) have varied from year to year. The total number was 25.0/10, 000 in 1975 and 20.1/10, 000 in 2013. Screening campaigns and legislative changes have caused temporary increases. The highest incidence rates in different industrial sectors were in mining and quarrying (9.87; 95% CI: 8.65 to 11.30), construction (9.11; 95% CI: 9.98 to 10.43), manufacturing (9.04; 95% CI: 7.93 to 10.36) and in agriculture (8.78; 95% CI: 7.69 to 10.06), when financial sector was the reference (1.0). During that time, women had significantly less occupational diseases than men (RR 0.62; 95% CI: 0.57 to 0.68). There is a more distinct decreasing trend from 2005 onwards: the average annual change in incidence was e.g. in agriculture −9.2%, in transportation −10.3% and in construction −4.7%. The average annual decline was greatest in upper limb strain injuries (−11.1%). Discussion: This study provides a useful overview of the status of occupational diseases in Finland over several decades. These data are a valuable resource for investigating which occupations are at an increased risk and where the preventive actions should be focused on. It is important to study the long-term trends in the statistics of occupational diseases to discover the real trends behind year-to-year fluctuations.